How Do We Measure Social Management in Non-profit Organizations? A Scale Design Based on the Once Case - Moreno-Albarracín, Antonio Luis; Ortega-Rodríguez, Cristina; Álvarez-López, José Carlos; Núñez-Cacho, Pedro (Frontiers in Psychology, 2021)
One of the most important current challenges facing non-profit organizations (henceforth, NPOs) is to demonstrate that resources are being used properly to fulfil their missions. The development of control mechanisms to facilitate the measurement of social goal fulfilment has thus become a priority. In this context, transparency and good governance are configured as essential strategic elements to build trust with different stakeholders. In this work, we show the value provided by management indicators as they have become a necessary tool to confirm that the use of resources, internal processes and decisions within NPOs are carried out with the highest levels of efficiency and excellence. Only in this way can social credibility be achieved. The success of an NPO is inextricably linked to the support of donors, users, public administration and society as a whole. To achieve our research objective, we build a measurement scale based on the case of the Spanish National Organization for the Blind (ONCE), one of the largest Spanish NPOs. Based on ONCE´s experience, we propose a management indicator model that covers all social dimensions. The model is empirically validated to standardize the indicators for the ONCE and for serving as a reference for other entities.